Phase I Trial of a Yeast-Based Therapeutic Cancer Vaccine (GI-6301) Targeting the Transcription Factor Brachyury - Heery, Christopher R; Singh, B Harpreet; Rauckhorst, Myrna; Marté, Jennifer L; Donahue, Renee N; Grenga, Italia; Rodell, Timothy C; Dahut, William; Arlen, Philip M; Madan, Ravi A; Schlom, Jeffrey; Gulley, James L (Cancer immunology research, 2015)
The nuclear transcription factor brachyury has previously been shown to be a strong mediator of the epithelial-to-mesenchymal transition (EMT) in human carcinoma cells and a strong negative prognostic factor in several tumor types. Brachyury is overexpressed in a range of human carcinomas as well as in chordoma, a rare tumor for which there is no standard systemic therapy. Preclinical studies have shown that a recombinant Saccharomyces cerevisiae (yeast) vaccine encoding brachyury (GI-6301) can activate human T cells in vitro. A phase I dose-escalation (3+3 design) trial enrolled 34 patients at 4 dose levels [3, 3, 16, and 11 patients, respectively, at 4, 16, 40, and 80 yeast units (YU)]. Expansion cohorts were enrolled at 40- and 80-YU dose levels for analysis of immune response and clinical activity. We observed brachyury-specific T-cell immune responses in the majority of evaluable patients despite most having been heavily pretreated. No evidence of autoimmunity or other serious adverse events was observed. Two chordoma patients showed evidence of disease control (one mixed response and one partial response). A patient with colorectal carcinoma, who enrolled on study with a large progressing pelvic mass and rising carcinoembryonic antigen (CEA), remains on study for greater than 1 year with stable disease, evidence of decreased tumor density, and decreased serum CEA. This is the first-in-human study to demonstrate the safety and immunogenicity of this therapeutic cancer vaccine and provides the rationale for exploration in phase II studies. A randomized phase II chordoma study is now enrolling patients.